Pathways to Mental Health Care Services among Patients in Hospitals of Morang District, Nepal - Pradhan, Uma; Koirala, Namu; Parajuli, Surya B. (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: The burden of mental disorders is continuously growing globally. Limited or scarce resources, stigma, and discrimination can result in a lack of access to health and social service. Timely access to mental health care services and support systems are key in preventing and treating mental health disorders. Hence, this study aims to identify the mental health care seeking pathways in hospitals of Morang district. Methods: A cross-sectional study was conducted from January 2017 to December 2017 among patients attending psychiatric outpatient departments of two different hospitals of Morang district. One hundred patients were selected through consecutive sampling. A standard tool of the pathway to care from the catalog of WHO Psychiatric Assessment was used to collect the data. Data were analyzed using SPSS version 18. Chisquare test was used to find out the association between pathways and selected demographic variables at p<0.05 level of significance. Results: Among 100 participants, only 17% visited mental health care services directly. Remaining reached via non-psychiatric doctors (40%) and faith healers (37%). There was no significant association between the pathways to care, with age (p = 0.932), sex (p = 0.825), marital status (p = 0.348), education (p = 1.000), religion (p = 0.392), type of family (p = 0.381), monthly income (p = 0.590) and family history of mental illness (p = 0.730). Conclusion: Few patients visited mental health care services through direct pathways. There is a need to improve mental health awareness and advocate health workers as well as faith healers for better referral of patients with mental health problems.